2019
DOI: 10.1097/pec.0000000000001737
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-institutional Case Series With Review of Point-of-Care Ultrasound to Diagnose Malrotation and Midgut Volvulus in the Pediatric Emergency Department

Abstract: Point-of-care ultrasound can be used to screen for malrotation with and without volvulus in the newborn with bilious vomiting, as well as children with unexplained intermittent abdominal pain. We discuss cases where infants and children presenting to pediatric emergency departments with bilious vomiting and/or intermittent abdominal pain were initially screened for small bowel pathology with point-of-care ultrasound. Bedside findings suggestive of midgut volvulus were confirmed with radiology-performed ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…6,9,10 The diagnostic findings in Doppler US are twisting of SMV around SMA, namely whirlpool sign, and inversion of SMA and SMV course. 10,13 Although it is dependent on the experience of radiologist, it can also be performed as a fast diagnostic method called point-of-care US especially in emergency conditions. 13 However, normal SMA and SMV course does not exclude malrotation 14 as we found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9,10 The diagnostic findings in Doppler US are twisting of SMV around SMA, namely whirlpool sign, and inversion of SMA and SMV course. 10,13 Although it is dependent on the experience of radiologist, it can also be performed as a fast diagnostic method called point-of-care US especially in emergency conditions. 13 However, normal SMA and SMV course does not exclude malrotation 14 as we found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…10,13 Although it is dependent on the experience of radiologist, it can also be performed as a fast diagnostic method called point-of-care US especially in emergency conditions. 13 However, normal SMA and SMV course does not exclude malrotation 14 as we found in our study. In the present study, we performed Doppler US in 20 cases with high sensitivity (92.3%) but relatively lower specificity (85.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care ultrasound (POCUS) has been shown to be a useful adjunct for the evaluation of pediatric abdominal complaints 1–3 . Recent investigations have shown that POCUS performs similarly to radiology-performed ultrasound (RADUS) for the identification of intussusception, with a diagnostic accuracy ranging from 92% to 98% 4–9 .…”
mentioning
confidence: 99%
“…P oint-of-care ultrasound (POCUS) has been shown to be a useful adjunct for the evaluation of pediatric abdominal complaints. [1][2][3] Recent investigations have shown that POCUS performs similarly to radiology-performed ultrasound (RADUS) for the identification of intussusception, with a diagnostic accuracy ranging from 92% to 98%. [4][5][6][7][8][9] However, routine use of POCUS for the evaluation of intussusception has been limited, in part due to varying levels of sonography experience among staff members and the relative nascency of POCUS within the field of pediatric emergency medicine (PEM).…”
mentioning
confidence: 99%
“…If these two master sonographers could not, how could the rest of us? Some practices, mostly outside the United States, have further pursued US for the diagnosis of malrotation [3][4][5][6][7][8][9][10][11][12]. Some have achieved substantial success.…”
mentioning
confidence: 99%